The Effectiveness of Biosorbent from Chicken’s Egg Shell and Durian Peel towards the Quality of Biodiesel Product from Waste Cooking Oil - Kristanto, Dwi; Pudjihastuti, Isti; Amalia, Rizka (Vocational College of Universitas Diponegoro, 2021)
Indonesia is the largest exporter of palm oil with 85 - 90% of the world's total palm oil production. The consumption of palm oil in Indonesia is increasing every year, thus the waste are also increase. Waste cooking oil contains carcinogenic substances which causes various diseases. Biodiesel is an environmentally friendly substitute fuel for diesel made from vegetable oil as raw material. Used cooking oil can be used as raw material for biodiesel production, but it needs to be purified before further processing. Chicken egg shell contains 90% of CaCO3 can be used as a biosorbent of used cooking oil. Durian skin contains 50% - 60% of cellulose also has the potential as a biosorbent. This research was conducted to investigated the effectiveness of the combination of chicken egg shell biosorbent with durian skin for the purification process of used cooking oil as a raw material of biodiesel. Biosorbent was produced by carbonization process in a furnace at a temperature of 550oC for durian skin and 9000C for chicken egg shells. The results show that the acid number of used cooking oil has met the parameters of the SNI 3741: 2013, namely 0.43 mgKOH / gr and FFA levels of 0.0024% with a yield of 62.76%. The purified cooking oil was then continued with the transesterification process to produced biodiesel. The biodiesel obtained had the cetane numbers B100 of 33.8 and B30 of 45.2.